Internalisasi Nilai Moderasi Beragama pada Era Digital di SMA Wahid Hasyim Model Sumberwudi Karanggeneng Lamongan - Nabila Putri; Zuli Dwi Rahmawati; Sauqi Futaqi (Pascasarjana IAI Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the process of internalizing religious moderation values in the digital era, the roles of teachers and school authorities in instilling religious moderation values through digital media utilization, and the supporting and inhibiting factors at SMA Wahid Hasyim Sumberwudi Karanggeneng Lamongan. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research informants consisted of the principal, Islamic Religious Education teachers, and students. Data were analyzed using the Miles, Huberman, and Saldana model, including data condensation, data display, and conclusion drawing. The findings revealed that the internalization of religious moderation values was carried out through classroom learning, religious activities, habituation of tolerance, teacher role modeling, and the utilization of digital media. Teachers and school authorities acted as educators, mentors, and supervisors in guiding the wise use of digital media. Supporting factors included a conducive school environment, routine religious activities, collaboration between teachers and parents, and the use of digital media. Inhibiting factors consisted of social media influence, unverified religious information, and students' limited understanding of religious moderation.